Distinct effects of AMPA receptor subunit depletion on spatial memory - Eltokhi, A; Bertocchi, I; Rozov, A; Taylor, A; Rawlins, JNP; Bannerman, DM (Cell Press, 2023)
Pharmacological studies established a role for AMPARs in the mammalian forebrain in spatial memory performance. Here we generated global GluA1/3 double knockout mice (Gria1/3−/−) and conditional knockouts lacking GluA1 and GluA3 AMPAR subunits specifically from principal cells across the forebrain (Gria1/3ΔFb). In both models, loss of GluA1 and GluA3 resulted in reduced hippocampal GluA2 and increased levels of the NMDAR subunit GluN2A. Electrically-evoked AMPAR-mediated EPSPs were greatly diminished, and there was an absence of tetanus-induced LTP. Gria1/3−/− mice showed premature mortality. Gria1/3ΔFb mice were viable, and their memory performance could be analyzed. In the Morris water maze (MWM), Gria1/3ΔFb mice showed profound long-term memory deficits, in marked contrast to the normal MWM learning previously seen in single Gria1−/− and Gria3−/− knockout mice. Our results suggest a redundancy of function within the pool of available ionotropic glutamate receptors for long-term spatial memory performance.